Evaluation of DOAC-Stop to Reverse the Effects of Factor XIa Inhibitors on the Activated Partial Thromboplastin Time - Fitzpatrick, Ella K. (My University, 2025)
Factor (F) XI is a serine protease involved in the intrinsic pathway of coagulation. This protein is an emerging target for anticoagulation due to its presumed minor role in hemostasis, but major role in thrombosis. FXI and activated FXI (FXIa) inhibitors are promising alternatives to traditional anticoagulants like vitamin K antagonists and heparins, and newer therapies like direct oral anticoagulants (DOACs), which target thrombin or FXa. Coagulation tests, like the activated partial thromboplastin time (APTT), are critical for evaluating the clotting pathways. Notably, the APTT is used to diagnose antiphospholipid syndrome (APS), which is an autoimmune disease that increases the risk of thrombosis. Since DOACs selectively inhibit coagulation, they prolong the APTT and can potentially mimic patterns characteristic of an underlying coagulation disorder like APS. As a consequence, in patients receiving DOAC therapy, it becomes challenging to distinguish between the inhibitory effects of DOACs and indicators of a pathological condition. Current strategies to address DOAC interference have significant disadvantages. DOAC-Stop™ (DS) is an activated charcoal-based compound that adsorbs molecules such as DOACs. Studies show that DS reverses the effects of dabigatran, apixaban, edoxaban, and rivaroxaban on the APTT. However, it remains unknown whether DS is capable of reversing the effects of new FXI(a) inhibitors. This thesis aims to determine whether DS reverses the effects of asundexian, milvexian, and abelacimab on the APTT. We first establish that the FXI(a) inhibitors prolong the APTT. We then show that DS reverses the effects of asundexian and milvexian on the APTT, but not abelacimab. Additionally, we show that DS distinguishes between the effects of milvexian and heparin. These findings suggest that DS may serve as a potential method to reverse the effects of asundexian and milvexian on the APTT and to distinguish their effects from that of heparin.
DOAC-Stop Reversal of FXIa Inhibitors
Keywords: anticoagulation; factor XI; factor XI inhibitors; activated charcoal